PENGGUNAAN MEDIA PROYEKTOR DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SEJARAH DI KELAS XI IPS 1 SMA NEGERI 9 PALU - Mutawakkil Mutawakkil; Putri Dewi Puspita (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2018)
This study is a classroom action research conducted in 2 cycles consisting of four stages: planning, action implementation, observation and reflection. The result of analysis of affective assessment on pre action of student number 20 people expressed 4 and 4 unfinished students and the highest score was 79,5 and lowest score 32. The result of analysis obtained by students on activity of cycle I, there was an increase in affective appraisal and psychomotor using projector media. The result of affective appraisal showed 7 complete and unfinished students as many as 13 people with the highest score of 85.5 and the lowest score 58,8. While psychomotor assessment showed a complete student 4 and unfinished students 16 people with the highest score of 86.7 and the lowest score of 60.5. In cycle II there is a better improvement of affective and psychomotor assessment. The results of affective assessment showed a complete student as many as 19 people and students who do not complete as many as 1 person with a high score of 92.1 and a low score of 73.8. While the results of psychomotor assessment showed a complete student as many as 20 people with the highest score 92.1 and the lowest score 79.3. Performance of teachers also increased, in cycle I obtained a percentage of 78.33% and on the second cycle obtained percentage of 95%. Student activity in learning process also increase, in cycle I got percentage equal to 63,63% and in cycle II obtained percentage equal to 90,90%. These results can be concluded that the use of media projectors can improve student learning motivation in class XI IPS I SMA Negeri 9 Palu.